Cellular vulnerabilities of glioblastoma - Merisaari, Joni (fi=Turun yliopisto|en=University of Turku|, 2021)
Glioblastoma (GB) is the most fatal and frequent malignant brain tumor, and it is driven by multiple oncogenic pathways. Despite intensive screening of genomic, transcriptomic, metabolic, and post-translational landscape of GB, targeted therapies have provided no improvements for the survival of GB patients. This incurability of GB is due to its infiltrative growth, intratumoral heterogeneity and intrinsic resistance towards treatment modalities which are driven by its subpopulations, such as glioblastoma stem cells (GSCs). Therefore, it is crucial to try to understand the mechanisms of GBs cellular resistance and potential vulnerabilities of GSCs. In this thesis we demonstrate alternative targets for GB therapy. Protein phosphatase 2A (PP2A) is inhibited in GB by non-genetic mechanisms, therefore, its therapeutic reactivation is possible. We described that small molecule reactivators of PP2A (SMAPs) efficiently cross the blood-brain barrier (BBB) and exhibit robust cytotoxicity towards heterogenous GB cell lines. Furthermore, we present specific kinases which inhibition induce synthetic lethality under PP2A reactivation. Collectively, these studies present SMAPs as a novel therapy for GB and propose an alternatives for multikinase inhibitors. In GB, nanoparticles have been researched for their potential to circumvent insufficient drug properties. However, opposed to traditional utilization of nanoparticles, we discovered an alternative use of them in GB. We demonstrated that mesoporous silica nanoparticles (MSNs) functionalized with polyethylenimine (PEI) induce cell death specifically in GSCs. The PEI-MSNs accumulated in the lysosomes of GSCs and caused lysosomal membrane permeabilization potentially through proton sponge effect. Furthermore, we determined that PEI-MSNs efficiently cross the BBB in mice. In summary, this thesis presents a novel therapy concepts for GB.

Glioblastooman solutason haavoittuvuudet Glioblastooma (GB) on yleisin ja pahanlaatuisin aivosyöpä, jossa useat onkogeeniset signalointipolut ovat yliaktiivisia. Huolimatta genomiikan, transkriptomiikan, metabolomiikan ja translaation jälkeisten muutosten intensiivisestä seulonnasta GB:ssa, kohdennetut hoidot eivät ole tuottaneen lisäelinaikaa GB-potilaille. GB:n hoidon vaikeus johtuu sen infiltratiivisesta kasvusta, kasvaimen sisäisestä heterogeenisyydestä ja synnynnäisestä resistenssistä hoitoja vastaan. Syynä näihin on usein glioblastooman kantasolut. Tästä syystä, on erittäin tärkeää pyrkiä ymmärtämään GB:n solutason resistanssimekanismeja ja glioblastooman kantasolujen potentiaalisia heikkouksia. Tässä väitöskirjassa esitämme uusia kohteita GB:n hoitoon. GB:ssa proteiinifosfataasi 2A (PP2A) on estetty muilla tavoin kuin geneettisillä mekanismeilla. Tästä syystä sen terapeuttinen uudelleenaktivointi on mahdollista. Osoitimme tutkimuksissamme, että pienimolekyyliset PP2A aktivaattorit (SMAP) läpäisevät veri-aivoesteen ja ovat sytotoksisia GB:n heterogeenisiä solulinjoja kohtaan. Tämän lisäksi selvitimme, minkä kinaasien hiljentäminen altistaa GBsoluja entisestään PP2A:n aktivaatiolle. Yhteenvetona tutkimus esittää SMAP lääkkeet uutena terapiamuotona GB:n hoitoon ja ehdottaa vaihtoehtoja multikinaasiestäjille. Nanopartikkelitutkimus GB:aan liittyen on pääasiassa pyrkinyt parantamaan lääkkeiden ominaisuuksia. Me löysimme kuitenkin vaihtoehtoisen tavan käyttää nanopartikkeleita GB:ssa. Osoitimme, että mesohuokoiset piioksidi-nanopartikkelit, jotka on pinnoitettu polyetyyliemiinillä, aiheuttavat solukuoleman glioblastooman kantasoluissa. Kyseiset nanopartikkelit kerääntyivät glioblastooman kantasolujen lysosomeihin ja aiheuttivat sen membraanin tuhoutumisen ”proton sponge” efektin avulla. Kokonaisuudessaan väitöskirja esittää uusia heikkouksia glioblastooman kantasoluissa.